Thai elite networks as an example of an extractive institution - Gliniak, Paweł (Relacje tajlandzkich elit jako przykład instytucji oligarchicznej, 2021)
The main research objective of this article is to analyse the influence of Thai elites on the socio-economic development of the country from the institutional economic and new institutional economics (NIE) perspective. The specific research goals included an introduction of the views of institutional economics and NIE on economic development and to present the country’s modernization process since World War II. Other goals were to explain the relationship between the Thai elites, and study the quality of institutions using indicators such as the Democracy Index, the Rule of Law Index, and the World Governance Indicator. The article aims to fill the research gap related to analysing the impact of an institution on socio-economic development. In this case, this is an extractive institution: the network monarchy. The Thai elites’ activities, which only serve their own interests, exacerbate the problems experienced by the country. The research carried out for this article shows the entire Thai institutional environment is in poor shape, and negatively affects all aspects of the daily lives of Thai citizens. Corruption in the government is widespread. The rule of law has seen no improvement, and the judiciary is ineffective. The democratic process has been slowed down if not practically halted. Freedom of speech is widely restricted, and the ruling military junta stifles opposition in a bid to maintain the status quo. This article is interdisciplinary. In addition to economics, it addresses political science, sociology and aspects of the law. The research results contained in this article allow for a deeper understanding of Thailand’s economic changes and aim to encourage further economic analysis from an institutional economics angle.
Ekonomia XXI Wieku = Economics of the 21st Century, 2021, Nr 24, s. 39-55
Keywords: Thailand; institutions; oligarchy; institutional economics; economic development; Tajlandia; instytucje; oligarchia; ekonomia instytucjonalna; rozwój gospodarczy